0046 Mortality study of a cohort of chemical workers producing perfluorinated derivatives and other chemicals. (21st August 2017) - Girardi, Paolo; Merler, Enzo
Abstract : Since 1968 a single factory (Veneto Region, Italy) has been the largest manufacturer of perfluorinated derivates (PF) in UE. Intermediates for pharmaceutical and crop protection chemicals have been also produced. In total 609 subjects have been employed since production began. PF are manufactured by electrochemical fluorination. Higher homologues are no longer produced since 2012. Nowadays, a groundwater pollution of PF is involving the water supplies for a population of about 1 10 000 inhabitants. As a first step for an evaluation of long-term health effects, we conducted a retrospective cohort mortality study on male employees, hired before year 2004, at work for at least one year, followed up until June 2016 (415 subjects), using the regional mortality rates as a reference. High serum levels of perfluorooctanoic acid (PFOA) have been detected since year 2000 covering 121 workers (median PFOA concentration, 1817 ng/g; range, 166 ng/g for nonexposed workers to 5101 ng/g for directly exposed workers). The cohort as a whole (12, 449 PYs, 79 deaths) expresses an unexpected over-mortality (SMR: 1.07; 95% CI: 0.86–1.34), mainly due to liver cirrhosis and liver tumours. The subset of employees with a certain exposure to PFOA (plant operator, maintenance and laboratory workers) (2, 351 PYs, 22 deaths) shows an higher overall mortality (SMR=1.48 95% CI 0.98–2.33) and a statistically significant excess of deaths from diseases of the circulatory system (infarct; SMR: 7.21; 95% CI: 1.80–28.85) and diabetes (SMR: 6.75; 95% CI: 1.69–26.99). The study suffers from the limited size, and mortality is not an appropriate end-point for some diseases of interest.